Venous and Arterial Responses to Partial Gravity - Lee, Stuart M. C.; Martin, David S.; Miller, Christopher A.; Scott, Jessica M.; Laurie, Steven S.; Macias, Brandon R.; Mercaldo, Nathaniel D.; Ploutz-Snyder, Lori; Stenger, Michael B. (Frontiers in Physiology, 2020)
Introduction. Chronic exposure to the weightlessness-induced cephalad fluid shift is hypothesized to be a primary contributor to the development of Spaceflight Associated Neuro-ocular Syndrome (SANS) and may be associated with an increased risk of venous thrombosis in the jugular vein. This study characterized the relationship between gravitational level (G-level) and acute vascular changes. Methods. Internal jugular vein (IJV) cross-sectional area, inferior vena cava (IVC) diameter, and common carotid artery (CCA) flow were measured using ultrasound in 9 subjects (5F, 4M) while seated when exposed to 1.00-G, 0.75-G, 0.50-G, and 0.25-G during parabolic flight and while supine before flight (0-G analog). Additionally, IJV flow patterns were characterized. Results. IJV cross-sectional area progressively increased from 12 (95% CI: 9-16) mm2 during 1.00-G seated to 24 (13-35), 34 (21-46), 68 (40-97), and 103 (75-131) mm2 while seated during 0.75-G, 0.50-G, and 0.25-G and 1.00-G supine, respectively. Also, IJV flow pattern shifted from the continuous forward flow observed during 1.00-G and 0.75-G seated to pulsatile flow during 0.50-G seated, 0.25-G seated, and 1.00-G supine. In contrast, we were unable to detect differences in IVC diameter measured during 1.00-G seated and any level of partial gravity or during 1.00-G supine. CCA blood flow during 1.00-G seated was significantly less than 0.75-G and 1.00-G supine, but differences were not detected at partial gravity levels 0.50-G and 0.25-G. Conclusions. Acute exposure to decreasing G-levels are associated with an expansion of the IJV and flow patterns that become similar to those observed in supine subjects and in astronauts during spaceflight. These data suggest that G-levels greater than 0.50-G may be required to reduce the weightlessness-induced headward fluid shift that may contribute to the risks of SANS and venous thrombosis during spaceflight.